Santri Punk: Identity Hybridization within the Pesantren Community - El Mubarok, Ahmad Mufarrih (Institut Agama Islam Negeri Kerinci, 2024)
Pesantren, as religious educational institutions, play a crucial role in shaping Muslim intellectuals. However, the emergence of the “santri punk” phenomenon within pesantren indicates a new dynamic that challenges the traditional religious image of these institutions. This study aims to explore the motives behind the construction of the santri punk identity at Pantura Lamongan pesantren and to analyze the influence of identity status in this process. Using a qualitative approach, data were collected through individual life history methods and interviews, then examined through Alfred Schutz’s phenomenological theory and James Marcia’s identity status concept. The findings reveal that the formation of santri punk is influenced by “because motives,” such as shock culture, difficulties in social interaction, and cultural encounters, as well as “in order to motives,” including the pursuit of solidarity, social identity, and self-actualization. This process is reinforced by identity crises experienced by santri aged 16–18 years, with a tendency toward identity achievement and identity moratorium statuses. External factors such as globalization, advancements in information technology, and the cultural characteristics of the Pantura region further accelerate the access to and adoption of punk culture within pesantren environments. These findings demonstrate that the santri punk identity represents a form of cultural hybridity within the context of pesantren’s social transformation.